Hubungan Kebugaran Kardiovaskuler Dengan Kualitas Kesehatan Fisik Pada Lansia Di PSTW Gau Mabaji Gowa - Syuaib, Miswani Mukani (Al-Hikmah, 2014)
The increasing number of elderly can cause a variety of problems, especially in terms of health and well-being of the elderly. The study aimed to determine the correlation of cardio respiratory fitness and physical health quality of the elderly in PSTW Gau Mabaji Gowa. The research design was a non-experimental (observational design) with the type of cross-sectional type. This research findings that almost elderly had good and very poor VO2 max (25, 8%). On other hand, almost elderly had bad quality of physical health (59, 7%). Cardio respiratory fitness had significant correlations with the physical health (p=0,001). The most influential variable on the physical health was the variable of maximum oxygen consumption (OR: 8.333).